2007
DOI: 10.1111/j.1348-0421.2007.tb04005.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses of Mice to Influenza Subunit Vaccine in Combination with CIA07 as an Adjuvant

Abstract: CIA07 is an immunostimulatory agent composed of E. coli DNA fragments and modified LPS lacking the lipid A moiety. In this study, we investigated whether CIA07 promotes immune responses as an adjuvant to the influenza subunit vaccine. Balb/c mice were immunized intramuscularly once or twice at a 4-week interval with the trivalent influenza subunit vaccine antigen alone or in combination with CIA07 as adjuvant. Antigen-specific serum antibody titers and hemagglutination-inhibition (HI) antibody titers were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…We also observed that CIA05 stimulates secretion of various cytokines and chemokines from human monocytes as well as mouse bone marrow dendritic cells, and the immunostimulating activity of CIA05 was higher than that of MPL (manuscript in preparation). In our previous studies, CIA05, when used alone or in combination with bacterial DNA fragmented into optimal sizes, enhanced the immunogenicity of HBsAg and influenza virus subunit vaccine [17,29]. In addition, formulation of CIA05 plus Gardasil®, which consists of HPV L1 VLPs adjuvanted with alum, significantly increased splenic IFN-γ secretion as well as the serum antibody responses, indicating that CIA05 is able to stimulate both Th1-and Th2-type immune responses in concert with alum [18].…”
Section: Discussionmentioning
confidence: 92%
“…We also observed that CIA05 stimulates secretion of various cytokines and chemokines from human monocytes as well as mouse bone marrow dendritic cells, and the immunostimulating activity of CIA05 was higher than that of MPL (manuscript in preparation). In our previous studies, CIA05, when used alone or in combination with bacterial DNA fragmented into optimal sizes, enhanced the immunogenicity of HBsAg and influenza virus subunit vaccine [17,29]. In addition, formulation of CIA05 plus Gardasil®, which consists of HPV L1 VLPs adjuvanted with alum, significantly increased splenic IFN-γ secretion as well as the serum antibody responses, indicating that CIA05 is able to stimulate both Th1-and Th2-type immune responses in concert with alum [18].…”
Section: Discussionmentioning
confidence: 92%
“…CIA07, a mixture of CIA02 and CIA05 at a ratio of 100:1, further promoted the immune responses to HBsAg. It also elicited stronger immune responses when administered with influenza virus subunit vaccine antigen [21]. In addition, CIA07 was observed to have higher antitumor activity in a mouse bladder cancer model than Bacillus Calmette-Guerin, which is in current clinical use as immunotherapy for bladder cancer [22].…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 97%
“…CIA07 exhibited significantly higher antitumor activity in a mouse bladder cancer model than BCG, which is currently used as immunotherapy for bladder cancer (Cho et al, 2006. It also showed an adjuvant activity to two viral vaccine antigens, HBsAg and influenza virus subunit vaccine Park et al, 2007). In this study, we examined the potential of CIA07 as an adjuvant in a vaccine against infection with the bacterial pathogen, B. anthracis.…”
Section: Introductionmentioning
confidence: 98%